Economic benefits of corporate E-learning - Dimitrova, Joana Dimitrova (Yearbook Telecommunications, 2019)
Businesses value online training as a cost-effective, convenient and efficient way of delivering corporate education. The purpose of this report is to examine and analyze models for measuring the benefits and return on investment of corporate training. It is a matter of creating and executing a solid strategy. The results of the report show that measurements, including ROI, are determined by the training and business needs of the company. This report contributes by examining and analyzing the measurement models of Kirkpatrick and Phillips’ learning outcomes in the light of eLearning, as well as the methods for assessing the quality of eLearning content. The contribution of the report to research is that it can be used as a basis for exploring a more robust methodology for measuring e-learning outcomes.